PENINGKATAN KEMAMPUAN BAHASA INGGRIS DAN ARAB PADA TINGKAT SD DAN SMP SEBAGAI PERSIAPAN ERA SOCIETY 5.0 DI KAMPUNG RAKYAT KABUPATEN LABUHANBATU SELATAN - Marwah; Nurlida Asni; Istiqamah Ardila (Yayasan Baitul Hikmah al-Zain, 2024)
Studying English and Arabic has become a necessity amidst the dynamics of current developments, especially in the current era of Society 5.0. This era has a basic concept in the form of transforming a conventional way of life into a digital one. One of the challenges that awaits the world of education in the Society 5.0 era is how to bring together science and technology without sacrificing students. Through this service the author wants to identify and describe the challenges faced by English and Arabic in the era of society 5.0 based on the use of interactive applications through guidance and English and Arabic learning videos. The results of this service explain that teachers must have special skills to optimize the use of technology in the learning process, so that students can absorb more of the material. All parties and stakeholders involved in English and Arabic learning activities must be willing to improve so that they are able to maintain their existence in this digital era.